Adoption Levels Against Farmer Cultivation Technology Soybean (Glycine Max L) On the Influence of Socio-economic foundation in the District of South Kualuh North Labuhan Batu Regency - Iman, Arman; FS, Harahap (International Journal of Science, Technology & Management, 2021)
In running a farming business in an agricultural production organization, farmers as actors and implementers carry out organizing agricultural cultivation, labor, and capital aimed at production in the agricultural field, whether based on profit or not. Cultivation of soybean (Glycine max L.) is the main commodity of legumes which is a national mainstay because the source of vegetable protein is important for food diversification in supporting national food security. Many factors influence farmers in farming, especially in terms of prioritizing optimal production results, including economic factors with capital control so that the expectation of greater profits from farming will be chosen when compared to other forms of farming. The research objective was to determine the level of farmer adoption of soybean cultivation technology and to determine the socio-economic effect of farmers on soybean cultivation technology in Sidua Dua Village, Kualuh Selatan District, North Labuhanbatu Regency. This research uses descriptive or quantitative methods by conducting survey methods. From the results of the study, it was found that the Farmer's Adoption Rate of Soybean Cultivation Technology (Glycine Max L) on the Influence of Socio-Economic Aspects in Kualuh Selatan District, North Labuhanbatu Regency was classified as moderate, soybean cultivation had not followed all the components of cultivation technology recommended by Field Agricultural Instructor and the level of adoption of soybean cultivation in Sidodadi village is influenced by age, level of education, length of farming, frequency of attending counseling.